Ana M. López : Essays. - López, Ana M. (State University of New York Press, 2023)
Brings together Ana M. López's field-defining essays on Latin American film and media in one indispensable volume.
Keywords: Motion pictures -- Latin America -- History.; Motion pictures -- Social aspects -- Latin America.; Mass media -- Latin America -- History.; Mass media -- Social aspects -- Latin America.; Latin Americans in motion pictures.; Cinéma -- Amérique latine -- Histoire.; Cinéma -- Aspect social -- Amérique latine.; Médias -- Amérique latine -- Histoire.; Médias -- Aspect social -- Amérique latine.; Latino-Américains au cinéma.; History & Criticism.; Latin America.; HISTORY.; Radio.; PERFORMING ARTS.; Television.; Film & Video.; Latin Americans in motion pictures; Mass media; Mass media -- Social aspects; Motion pictures; Motion pictures -- Social aspects; Latin America; Electronic books.; History